Prediction of fatigue crack propagation in bulb stiffeners by experimental and numerical methods. (June 2017) - Yue, Jingxia; Dang, Zhifan; Guedes Soares, C.
Highlights: This paper proposes a method to calculate the fatigue crack propagation in bulbs. The shape of a 3D surface crack in the bulb stiffener was measured and estimated by the NCOD method. The obtained crack shape was used to predict the fatigue crack propagation based on the 2D Paris' law and FEM. The predicted fatigue crack propagation has been verified by the full-scale fatigue test on a typical detail. Abstract: Fatigue crack propagation in bulb stiffeners, which are widely used in ship and bridge structures, is one of the basic problems for structures' fatigue life prediction. This paper proposes a method to calculate the fatigue crack propagation in bulbs, which provides a method for defining the failure criterion for bulb stiffeners. The shape of a three dimensional surface crack in a full-scale bulb stiffener fatigue test was measured and estimated by the Nominalization Crack Opening Displacement method. Then the obtained crack shape was used to predict the fatigue crack propagation in the bulb stiffener based on the two dimensional Paris' law and the Linear Finite Element Analysis method. Moreover, the predicted fatigue crack propagation has been verified by the full-scale fatigue test on a typical ship structure detail.